Chitosan-clay nanocomposite as a drug delivery system of ibuprofen (Research, Society and Development, 2022)
Chitosan/montmorillonite nanocomposite films were prepared by the solvent evaporation method to immobilize the drug ibuprofen (IBU) and delay its release in a medium that simulates the environment of the gastrointestinal tract. The effects of montmorillonite, at different mass proportions (10, 20, and 50%), on the morphological and physical properties of the films were studied. The samples were characterized by X-ray diffraction (XRD), Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), degree of swelling, drug encapsulation, and drug release efficiency. According to the XRD it was evidenced that the incorporation of montmorillonite to chitosan led to the formation of nanocomposites of ordered morphology. The infrared spectra confirmed the good interaction between montmorillonite and chitosan by the formation of nanocomposites. This fact, which favored the imprisonment of the IBU, reduced the diffusion coefficient in the studied systems. The micrographs comproved the formation of dense and uniform films. The controlled release profile, especially for the nanocomposite with 10% clay mass, showed a slow drug release rate. The incorporation of montmorillonite at different proportions produced different morphologies, with good encapsulation efficiency and an adequate profile for the controlled release of the drug.